2016
DOI: 10.1016/j.ejon.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of anxiety and depressive symptoms following breast cancer surgery and its impact on quality of life

Abstract: Purpose Little is known about the prevalence of combined anxiety and depressive symptoms (CADS) in breast cancer patients. Purpose was to evaluate for differences in demographic and clinical characteristics and quality of life (QOL) prior to breast cancer surgery among women classified into one of four distinct anxiety and/or depressive symptom groups. Methods A total of 335 patients completed measures of anxiety and depressive symptoms and QOL prior to and for 6 months following breast cancer surgery. Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 75 publications
1
70
0
6
Order By: Relevance
“…While the number and specific symptoms found in the psychological symptom cluster varied based on symptom assessment instruments used, all three of the studies of breast cancer patients undergoing CTX (Kim et al, 2008; Phligbua et al, 2013; Suwisith et al, 2008), as well as numerous studies of heterogeneous samples of oncology patients undergoing CTX (e.g., (Chen and Lin, 2007; Yates et al, 2015)), identified this symptom cluster. The ubiquitous nature of this symptom cluster confirms previous reports of the high prevalence rates for anxiety (Burgess et al, 2005; Gold et al, 2016; Lim et al, 2011) and depressive symptoms (Burgess et al, 2005; Dunn et al, 2011; Gold et al, 2016) in oncology patients undergoing cancer treatment.…”
Section: Discussionsupporting
confidence: 89%
“…While the number and specific symptoms found in the psychological symptom cluster varied based on symptom assessment instruments used, all three of the studies of breast cancer patients undergoing CTX (Kim et al, 2008; Phligbua et al, 2013; Suwisith et al, 2008), as well as numerous studies of heterogeneous samples of oncology patients undergoing CTX (e.g., (Chen and Lin, 2007; Yates et al, 2015)), identified this symptom cluster. The ubiquitous nature of this symptom cluster confirms previous reports of the high prevalence rates for anxiety (Burgess et al, 2005; Gold et al, 2016; Lim et al, 2011) and depressive symptoms (Burgess et al, 2005; Dunn et al, 2011; Gold et al, 2016) in oncology patients undergoing cancer treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Many patients, survivors, and their family members face uncertainty regarding whether cancer may return or progress . Fear, worry, or concern about this uncertainty, collectively called fear of cancer recurrence (FCR), has been associated with greater depression and poorer quality of life among cancer survivors . Studies also have reported that FCR among family caregivers sometimes is higher than that of their patients .…”
Section: Introductionmentioning
confidence: 99%
“…Studies also have reported that FCR among family caregivers sometimes is higher than that of their patients . Caregivers' FCR that their patient's cancer may return or progress has been associated with their own greater anxiety, depression, and loneliness, and a poorer quality of life as well …”
Section: Introductionmentioning
confidence: 99%
“…PNB-028 reduces depression and anxiety. Depression and anxiety are serious cancer-associated symptoms (28). CCK peptides alter neurological functions to promote depression and anxiety (29).…”
Section: Pnb-028 Modulates Expression Of Genes Involved In Cancermentioning
confidence: 99%